MINAT MAHASISWA PRODI S1 PENDIDIKAN TEKNIK MESIN UNIVERSITAS NEGERI PADANG TERHADAP PEKERJAAN PROFESI GURU VOKASI - Fadli Ramadhan; Budi Syahri; Yolli Fernanda; Febri Prasetya (Jurnal Vokasi Mekanika (VoMek), 2024)
In the era of globalisation, education plays an important role in creating a prosperous society. Teachers have a crucial role in improving the quality of education in Indonesia. Interest in becoming a teacher is a condition in which a person has great attention to the teaching profession, feels happy, and wants to become a teacher. This study aims to identify the interest of undergraduate Mechanical Engineering Education Study Programme students in choosing a profession as a teacher. Based on observations and interviews with students of the Mechanical Engineering Education Study Programme, Faculty of Engineering, Padang State University, it is known that many students are not interested in becoming teachers. Some of the reasons underlying this include lack of self-confidence, doubts about income, opportunities to become a teacher, and personal ability to deal with student characteristics. This study aims to determine the description of interest in becoming a teacher in Mechanical Engineering Education Study Programme students at Padang State University. The research method used is descriptive with a quantitative approach, with a sample of 25% of the population or 43 people. The results showed that the interest of Mechanical Engineering Education Study Programme students at Padang State University towards the vocational teaching profession reached 81.36%, which is included in the good category. In conclusion, students of Mechanical Engineering Education Study Programme at Padang State University have a good interest in becoming a teacher.